REVIEW: MENINGKATKAN POPULASI TERNAK BABI MELALUI TEKNOLOGI REPRODUKSI PASCA AFRICAN SWINE FEVER - Korbinianus Feribertus Rinca (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
The purpose of writing this review is to determine the role of reproductive technology in increasing the population of pigs after the African Swine Fever (ASF) outbreak. The method used in writing this review is to search for published research articles using Google search and Science direct with the keywords African swine fever and Artificial Insemination (AI). The results of this review show that ASF can reduce the population due to the high mortality rate, ASF can be transmitted through the reproductive organs but this can be overcome by utilizing IB reproductive technology. In addition, AI reproductive technology is also one of the reproductive technologies that can be used to increase the livestock population after the ASF outbreak. Based on the review, it can be ensured that artificial insemination reproductive technology is able to prevent ASF transmission and increase livestock populations after the ASF outbreak.